Functions and mechanisms of lncRNAs in immune escape and their application in immunotherapy for colorectal cancer - Dechun Zhang; Shaoxuan Pei; Zixuan Feng; Guangfeng Xia (Journal of Translational Medicine)
Abstract Recent studies have progressively clarified the critical role of long non-coding RNA (lncRNA) in cancer, especially concerning its involvement in immune processes, which holds significant therapeutic promise. However, the incorporation of lncRNA into immunotherapy has yet to demonstrate adequate clinical efficacy. This shortcoming can be attributed to various challenges, including unclear mechanisms of action and limited prognostic capacity. In colorectal cancer (CRC), this ineffectiveness may predominantly stem from immune escape mechanisms mediated by lncRNAs. Despite some exploration into lncRNA-driven immune escape, a comprehensive overview of its implications for immunotherapy in CRC remains inadequately addressed. In this review, we thoroughly assess the role of lncRNA in immune escape mechanisms associated with CRC, focusing on immune checkpoints, immune cells, and cytokines. We elucidate the relationship between lncRNA-mediated immune escape and CRC progression and discuss strategies for lncRNA-mediated immunotherapy for CRC. Our aim is to provide fresh insights into the potential of targeting lncRNAs to enhance the effectiveness of immunotherapeutic strategies in CRC.